Meningkatkan Penguasaan Kosakata Baku dan Tidak Baku Melalui Model Kooperatif Tipe Index Card Match Menggunakan Aplikasi Zoom Kelas VI - Indrawati, Dini (Journal of Academia Perspectives, 2022)
In the learning process, the teacher is expected to provide teaching which is easily understood by students. However, there are some teachers who have not implemented the learning model in every learning process. The solution which can be taken by teachers is to use the index card match learning model. The index card match learning model or matching pair cards is one type of cooperative learning. The index card match learning model is varied by utilizing card media in order to improve student learning outcomes in mastering standard and non-standard vocabulary. This study aims to determine teacher and student activities, student learning outcomes, and student responses. The subjects in this study were sixth grade students of SDN Bahagia 06, totaling 20 students. The data collection instrument was carried out using teacher and student activity observation sheets, tests, and student questionnaires/response sheets. Data analysis used descriptive statistics of percentages. The result of this study indicates that the result of observing teacher activities in the first cycle obtained an average value of 3.46, which is a moderate category. The second cycle obtained an average score of 4.83, which is an excellent category, and the third cycle obtained an average score of 4.94, which is an excellent category. On the other hand, the student activities in the first cycle obtained an average score of 3.40, which is a moderate category, the second cycle obtained an average value of 4.75, which is an excellent category, and in the third cycle the average score was 4.91, which is an excellent category. Moreover, student learning outcomes using the index card match model in the first cycle obtained 70%, which is a good category, then it increased in the second cycle by acquiring 90%, which is an excellent and a perfect category, and in the third cycle acquired 100% of the student completion in learning process, which is an excellent category.